Doctrine and Defence Transformation in Norway and Sweden. Issue 2 (23rd February 2016) - Kronvall, Olof; Petersson, Magnus
ABSTRACT: In this article we analyse to what degree the three functions of doctrine proposed by Harald Høiback – doctrine as a tool of operations, a tool of education, and a tool of change – have driven defence transformation in two Scandinavian states, Norway and Sweden. We conclude that doctrine, both allied and national, has had some impact on defence transformation in both countries: through the operations in Afghanistan, through education both at the branch level and joint level, and through organizational adaption to (first) the US 'RMA paradigm' and (later) to the subsequent 'COIN paradigm'. However, other factors, such as threat perception and defence spending, have also played an important role. It also remains to be seen whether the changes are ephemeral or of a more permanent nature.